AB0025 Activated Peripheral Naïve Human CD4+ T-Cells Express FcgrIII. (9th June 2015) - Bi, Y.; Chen, C.; Moore, T.L.; Chauhan, A.K.
Abstract : Background: Elevated levels of immune complexes (ICs) and aberrant T cell activation are two important features in autoimmunity (1). ICs engage Fc receptors (FcRs) and trigger cell specific functions (2). It is accepted that CD4 + T-cells do not express FcRs (3). We examined whether upon activation CD4 + T cells express FcγRIII, which is activated by ICs and signals via ITAM. Signaling via FcγRIII in CD4 + T cell could determine the outcome of these cells as this signal can overcome the inhibitory response during immune contraction by CTLA4 and PD1. Objectives: To establish the presence of FcγRIII on human CD4 + T-cells at protein and RNA transcript level. Methods: We examined the presence of FcγRIII using flow cytometry for binding of labeled ICs and anti-CD16 (3G8 & 245536 R&D system clone), We characterized the protein in Western blot experiments within the immunoprecipitates obtained by two anti-CD16 monoclonal antibodies. We then amplified the RNA transcripts using gene specific primers and sequenced the amplified product to confirm it to be FcγRIII product. The presence of the protein was further confirmed by cell staining using anti-CD16 antibodies. We compared and established the presence of FcγRIII in three cell types, CD4 + T-cells, Jurkat, P116 and activated CD4 + naïve T-cells. The protein sizes were also confirmed after reduction-alkylation and post N-glycanase digestion. Results: We showed specific CD4 + T-cell binding of labelled ICs that was competitively inhibited by anti-FcγRIII antibodies. Furthermore, we observed the presence of appropriate molecular mass protein in immunoprecipitates that were also present in peripheral human monocytes. Cell lysates analyzed directly in non-denaturing gel recognized a protein at ∼58-60kDa in Jurkat, P116 and monocytes obtained from two SLE patients, but not in the human foreskin fibroblast and embryonic kidney cell line 293T. Meanwhile, the immunoprecipitates after reduction-alkylation showed several protein bands at ∼30kDa, 53kDa and ∼75kDa, similar to previously reported peptides (4, 5). After reducing and alkylating, the bands in immunoprecipitated samples mainly shifted to lower positions from 20 to 37kDa. A prominent band at ∼21kDa appeared after digestion with N-glycanase which is the same as reported in polymorphonuclear cells (7). Sequencing of amplified transcripts confirmed it to be a product derived from the FCGR3A gene (gi: NM_001127596.1) Conclusions: Our results demonstrate induced expression of FcγRIII protein on activated peripheral CD4 + T-cells. References: Fairweather, D.L., Autoimmune disease mechanisms. eL.S. 2007 Takai, T., Fc receptors and their role in immune regulation and autoimmunity. Journal of clinical immunology. 2005, 25(1): 1-18 Takai, T. Role of Fc receptors in autoimmunity. Nature reviews immunology. 2002, 2(8):580-592. Clarkson, S.B., et al. CD16 Developmentaly regulated IgG Fc receptors on cultured humna monocytes. J. Exp. Med. 1988, 167(2): 408-420. Ory, P.A., et al. Characterization of polymorphic forms of Fc receptor III on human neutrophils. J of Clin. Invest. 1989, 83(5):1976 Huizinga, T.W. et al. Biallelic neutrophil Na-antigen system is assocaiated with a polymorphism on phospho-insitol-linked Fc gamma receptor III (CD16). Blood, 1990, 75(10: 213-217 Disclosure of Interest: None declared